Holocaust survivors in postwar Germany, 1945 - 1957 - Feinstein, Margarete Myers 1962- (Cambridge University Press, 2010)
Bamidbar: in the wilderness -- The living and the dead -- The new Jewish man and woman -- Guarantors of the future: DP children -- Performing identity and building community -- Out of the wilderness